65v-2=97v+3

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

6⋅(7v+3)=(5v-2)⋅9

Simplify 6⋅(7v+3).

Apply the distributive property.

6(7v)+6⋅3=(5v-2)⋅9

Multiply.

Multiply 7 by 6.

42v+6⋅3=(5v-2)⋅9

Multiply 6 by 3.

42v+18=(5v-2)⋅9

42v+18=(5v-2)⋅9

42v+18=(5v-2)⋅9

Simplify (5v-2)⋅9.

Apply the distributive property.

42v+18=5v⋅9-2⋅9

Multiply.

Multiply 9 by 5.

42v+18=45v-2⋅9

Multiply -2 by 9.

42v+18=45v-18

42v+18=45v-18

42v+18=45v-18

Move all terms containing v to the left side of the equation.

Subtract 45v from both sides of the equation.

42v+18-45v=-18

Subtract 45v from 42v.

-3v+18=-18

-3v+18=-18

Move all terms not containing v to the right side of the equation.

Subtract 18 from both sides of the equation.

-3v=-18-18

Subtract 18 from -18.

-3v=-36

-3v=-36

Divide each term by -3 and simplify.

Divide each term in -3v=-36 by -3.

-3v-3=-36-3

Cancel the common factor of -3.

Cancel the common factor.

-3v-3=-36-3

Divide v by 1.

v=-36-3

v=-36-3

Divide -36 by -3.

v=12

v=12

v=12

Solve for v 6/(5v-2)=9/(7v+3)